Kadar Imunoglobulin M Anti Phenolic Glycolipid-I Mycobacterium Leprae dan Tumor Necrosis Factor-α pada Penderita Lepra Subklinis - Yuanita Dian Utama; Soejoto Soejoto; Sri Djoko Susanto; ES Indrayanti; Subakir Subakir; Dhiana Ernawati (MEDIA MEDIKA INDONESIANA, 2010)
Immunoglobulin M anti phenolic glycolipid-I mycobacterium leprae level and tumor necrosis factor-α level in subclinical leprosyBackground: In subclinical leprosy, patients have no clinical lesion but seropositive to anti PGL-I antibody specific to M. leprae. On the other hand, TNF-α is produced in majority during innate immunity, inhibits mycobacterial growth and mediates granuloma formation. Mutant allele of TNF2308A has protective role against the development of severe form of leprosy. This study analyzed the correlation between IgM anti PGL-I and TNF-α levels in subclinical leprosy. Method: Study was done at an orphanage, using observational study with cross-sectional approach. Three mililiter peripheral blood were centrifuged and divided into 2 cryotubes. Immunoglobulin M anti PGL-I Mycobacterium leprae levels were measured by quantitative indirect ELISA. Tumor necrosis factor-α levels of subclinical leprosy patients (IgM anti PGL-I M. leprae level ≥600 U/mL) were measured using Human TNF-α ELISA Bender Medsystems for sandwich ELISA. Analysis of distribution normality using Shapiro-Wilk, continued with Rank Spearman correlation test.Result: Immunoglobulin M anti PGL-I levels were ranged between 616.85-1753.8 U/mL. Tumor necrosis factor-α levels were ranged between 2.72-50.13 pg/mL. There was significant positive correlation between IgM anti PGL-I level 600-1000 U/mL and TNF-α level (p=0.714; p=0.006), and insignificant negative correlation between IgM anti PGL-I level ≥1000 U/mL and TNF-α level (p=-0.172; p=0.557). Conclusion: There were significant positive correlation between IgM anti PGL-I level 600-1000 U/mL and TNF-α level, and insignificant negative correlation between IgM anti PGL-I level ≥1000 U/mL and TNF-α level. ABSTRAKLatar belakang: Pada lepra subklinis tidak dijumpai lesi, namun ditemukan antibodi anti PGL-I yang spesifik terhadap M. leprae. Di sisi lain, TNF-α dihasilkan terutama pada imunitas alami, dapat menghambat pertumbuhan mikobakteria dan memperantarai pembentukan granuloma. Alel mutan TNF2308A diketahui protektif mencegah berkembangnya bentuk lepra yang lebih berat. Penelitian ini menganalisis hubungan antara kadar IgM anti PGL-I dan TNF-α lepra subklinis.Metode: Penelitian dilakukan di sebuah panti asuhan secara observasional dengan pendekatan cross-sectional. Tiga mililiter darah perifer, disentrifus, kemudian dibagi dalam 2 cryotube. Pemeriksaan kadar IgM anti PGL-I M. leprae menggunakan ELISA indirek kuantitatif. Pada penderita lepra subklinis (kadar IgM anti PGL-I M. leprae ≥600 U/mL) diperiksa kadar TNF-α menggunakan ELISA sandwich dengan Human TNF-α ELISA Bender Medsystems. Analisis uji normalitas distribusi dengan Shapiro-Wilk, dilanjutkan uji korelasi Rank Spearman.Hasil: Kadar IgM anti PGL-I berkisar antara 616,85-1753,8 U/mL. Kadar TNF-α berkisar antara 2,72-50,13 pg/mL. Terdapat hubungan positif bermakna (p=0,714; p=0,006) antara kadar IgM anti PGL-I 600-1000 U/mL dan kadar TNF-α, dan hubungan negatif tidak bermakna (p=-0,172; p=0,557) antara kadar IgM anti PGL-I ≥1000 U/mL dan kadar TNF-α. Simpulan: Pada kadar IgM anti PGL-I 600-1000 U/mL, semakin tinggi kadar IgM anti PGL-I, semakin tinggi pula kadar TNF-α; sedangkan pada kadar IgM anti PGL-I ≥1000 U/mL terdapat kecenderungan hubungan terbalik yang tidak bermakna.